Abundance and Season Variability of Rove Beetles (Coleoptera: Staphylinidae) in the Mangrove Ecosystem of Akalapuzha Coastal Region, Kerala, South India - Krishna, V.R; Vineesh, P.J (HAYATI Journal of Biosciences, 2025)
The species composition and diversity of rove beetles (Staphylinidae) in the mangrove coastal region remain poorly explored, particularly in South India. This study aims to understand the rove beetle diversity in the Akalapuzha mangrove coastal ecosystem with respective seasonal changes (pre-summer, summer, and monsoon) as well as the efficacy of different collection methods (pitfall trap, light trap, Berlese funnel, and flotation method). From the study, the collected specimens came under five subfamilies: Oxytelinae, Aleocharinae, Staphylininae, Paederinae, and Tachyporinae. Among this, high taxa abundance was observed in Oxytelinae, followed by Aleocharinae, Staphylininae, Paederinae, and Tachyporinae. Among the documented subfamilies, three subfamilies, namely Oxytelinae, Staphylininae, and Aleocharinae were recorded in all three seasons. In the case of diversity analysis, the highest diversity was observed in the summer season (1-D = 0.277, & H = 0.630), followed by pre-summer (1-D = 0.306, & H = 0.678) and monsoon (1-D = 0.533, & H = 1.069). Among all the different insect collection methods, the flotation method (p